THE IMPORTANCE OF ANTHOCYANINS IN PLANTS - Tursunov Yakhyo Bokhadirovich; Ru’zimatova Shakhnoza Sirojiddin kizi (Web of Journals Publishing, 2025)
This article discusses the biological role of anthocyanins in plant life, their chemical structure, synthesis, and specific properties in color formation. Anthocyanins are found in various tissues of plants, provide their color diversity, and play an important role in adapting to environmental stress factors. Their effect on color depends on the pH level of the environment, metal ions, and other physicochemical factors. The article also provides information on the use of anthocyanins in the food industry and medicine. The results of the study contribute to a deeper understanding of the practical importance of anthocyanins in plant ecology and human activity.
Keywords: Anthocyanins, Flavonoids, Plant pigments, Color change, pH Level, Metal ions, Environmental stress, Biosynthesis, Food dyes, Cyanide.